Intrafamilial Transmission of Adult T Cell Leukemia Virus - Kajiyama, Wataru; Kashiwagi, Seizaburo; Ikematsu, Hideyuki; Hayashi, Jun; Nomura, Hideyuki; Okochi, Kazuo (The Journal of infectious diseases, 1986)
In an investigation of the mode of transmission of adult T cell leukemia virus (ATLV) in family settings, 275 male and 444 female subjects positive for antibody to ATLV-associated antigen (anti-ATLA) were studied. Their children were surveyed for anti-ATLA status. None of the 82 children of a positive father and a negative mother were positive for anti-ATLA. In contrast, the antibody prevalence among children with a positive mother and a positive or negative father was 27.9% and 19.9%, respectively. Of 39 parents who had one or more anti-ATLA-positive children <20 years old, 56.3% of the fathers and 97.1% of the mothers were anti-ATLA positive. Algorithm computation showed the possibility of ATLV transmission from husband to wife to be 60.8% and from wife to husband to be 0.4% over a 10-year period. These data suggest that ATLV is transmitted from mother to child and from husband to wife in family settings.